Performance of two cotton interspecific hybrids (Gossypium hirsutum L. × G. barbadense L.) in Greece: A comparative case study - Dimitrios BESLEMES; Antonios MAVROEIDIS; Evangelia TIGKA; Ioannis ROUSSIS; Panteleimon STAVROPOULOS; Dimitrios VATOUGIOS; Aikaterini TSELA; Aikaterini TSOPANOGLOU; Ioanna KAKABOUKI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2024)
Cotton (Gossypium hirsutum L.) is one of the most prominent and important industrial crops. In Greece, cotton farming occupies a significant share of the agricultural sector. However, the adverse effects of climate change have raised concerns regarding its performance in the near future, thus it is crucial to develop adaptation strategies for the production of cotton in Greece. One such alternative is the adoption of interspecific hybrids (G. hirsutum × G. barbadense). These hybrids have been suggested to be more resilient and to outperform their parental varieties. In order to evaluate the potential of such hybrids, a field experiment was conducted in two sites in Greece. Two novel cotton hybrids (1432 and 701) and a conventional variety (‘Elpida’) were farmed in two different plant densities (8 and 13 plants m2) and their agronomic traits (biomass, LAI), yield and yield components (seed cotton yield, lint yield, seed yield, ration lint/seed cotton, and ratio seed/seed cotton), and quality traits were assessed. The agronomic traits and the yield of the hybrids were equal or superior in comparison to ‘Elpida’. Similar findings were also observed in the majority of the quality traits. Based on our results, interspecific cotton hybrids are promising for the European cotton sector.